A promising choice in hypertension treatment: Fixed-dose combinations - Xinhuan Wan (Asian Journal of Pharmaceutical Sciences, 2014)
Obtaining the target blood pressure level by monotherapy can be challenging currently, especially for the patients who are suffering from other diseases meanwhile. It is demonstrated that a majority of hypertensive patients need two or more antihypertensive drugs to lower their blood pressure effectively. Consequently, fixed-dose which can be defined as that several active agents were combined in single pharmaceutical formulations appears to be a novel and underlying power in overcoming the cardiovascular disease. Based on the analysis of some literature and relative data from FDA, the advantages of fixed-dose combination are elucidated and formulations of common dual, triple-combinations were summarized. Clinical practices proved that fixed-dose combinations had many benefits comparing with single drug and separate agents in terms of effects, convenience, compliance, and costs to a certain extent. From the patients' perspective, the fixed-dose combination therapy will be increasingly utilized in blood pressure control in the future.